1977
DOI: 10.1152/ajpendo.1977.233.2.e104
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and growth hormone in lean and obese pigs.

Abstract: Plasma glucose, immunoreactive insulin (IRI), and growth hormone (GH) were determined in fasted lean and genetically obese pigs at 1, 3, and 6 mo of age. Rate of glucose clearance and plasma IRI and GH response in provocative stimulation were also measured. Fasting glucose was similar in lean and obese pigs, whereas glucose clearance rate was more rapid in lean pigs. Obese pigs were not hyperinsulinemic but had lower plasma GH than lean pigs. At 1 mo of age, both lean and obese pigs had higher plasma IRI and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…This result is due to differences in body composition, size and growth rate between the two types of pigs. The differences observed in our study are similar to those reported between Yorkshire pigs and Ossabaw pigs (Wangsness et al, 1977) an obese pig with a similar phenotype as the Mexican hairless pigs.…”
Section: Resultssupporting
confidence: 88%
“…This result is due to differences in body composition, size and growth rate between the two types of pigs. The differences observed in our study are similar to those reported between Yorkshire pigs and Ossabaw pigs (Wangsness et al, 1977) an obese pig with a similar phenotype as the Mexican hairless pigs.…”
Section: Resultssupporting
confidence: 88%
“…Buonomo and Klindt (1993) demonstrated differences in plasma IGF-1 concentrations between selected obese and lean genotypes in the neonate, being higher in the lean genotype, but found that these differences were diminished after 14 weeks of age (98 days), which would also agree with this study, since the pigs would be at least 150 days old (and even older in the slower growing Meishan X Landrace). Other studies of plasma GH concentrations indicated a suppressed GH status in pigs selected for high backfat, compared with those selected for lean (Althen and Gerrits, 1976;Wangsness, Martin and Gahagan, 1977), along with decreased foetal serum GH in preobese pigs (Martin et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Indwelling femoral artery catheters were surgically implanted in male castrate Yorkshire pigs (42 kg mean body weight) as described by Wangsness et al [11]: anesthesia was induced with sodium thiamylal and maintained with 2-4% halothanc in oxygen administered via tracheal intubation. Tygon microbore catheters that had been previously coated with heparin (TDMAC) were exteriorized to the back of the pig and closed with a two-way stopcock attached to a protective canvas patch glued to the animal's back.…”
Section: Surgery Animal Treatment and Serum Samplingmentioning
confidence: 99%